Creating a Culture of Independence - OECD (Organization for Economic Cooperation & Development, 2017)
Economic regulators ensure that infrastructure services are delivered efficiently, when competition on its own is unable to do so. This report explores how they carry out this task and the implications for infrastructure governance more broadly.